The Hokkien Rayas of Songkhla - Pimpraphai Bisalputra; Sng, Jeffery (The Journal of the Siam Society, 2020)
Of the numerous Chinese families in Thailand, perhaps fewer than ten can trace their ancestry back to the 18th century; one of these is the Wu clan of Songkhla. Wu Rang (吳陽), the patriarch, known locally as Hao Yiang, was part of a nascent Hokkien merchant community that thrived in Songkhla during the reign of King Borommakot (1733-1758) of Ayutthaya. Three prominent Thai-Chinese families trace their roots back to Hao Yiang, namely Na Songkhla, Suwankiri and Rochanahusdin. During the early Bangkok period the fortune of Songkhla rulers fluctuated depending on local conditions, Siamese demands, as well as center-periphery relations between the Siamese court and tributary principalities of the South. This article traces the story of the rulers of Songkhla from the late 18th century until the establishment of a centralized modern bureaucracy by King Rama V at the end of the 19th century.